2018
DOI: 10.1175/jpo-d-17-0104.1
|View full text |Cite
|
Sign up to set email alerts
|

The “Bag Breakup” Spume Droplet Generation Mechanism at High Winds. Part I: Spray Generation Function

Abstract: This paper describes the results of an experimental and theoretical investigation into the mechanisms by which spume droplets are generated by high winds. The experiments were performed in a high-speed wind-wave flume at friction velocities between 0.8 and 1.5 m s−1 (corresponding to a 10-m wind speed of 18–33 m s−1 under field conditions). High-speed video of the air–water interface revealed that the main types of spray-generating phenomena near the interface are “bag breakup” (similar to fragmentation of dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 38 publications
1
69
0
Order By: Relevance
“…Thus, in the present study, we follow Andreas and Emanuel () and Andreas () and inject droplets with initial velocities equal to the velocities of fluid particles in the surface wave, and the results are consistent with those obtained by Druzhinin et al (). Recent study by Troitskaya, Kandaurov, et al () suggests that the dominant mechanism of spume droplets generation is that of a bag‐breakup fragmentation. Troitskaya et al () and Troitskaya, Druzhinin, et al () developed a statistical description of the bag‐breakup phenomena, but PDF of the drops velocities at injection still remains unknown and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the present study, we follow Andreas and Emanuel () and Andreas () and inject droplets with initial velocities equal to the velocities of fluid particles in the surface wave, and the results are consistent with those obtained by Druzhinin et al (). Recent study by Troitskaya, Kandaurov, et al () suggests that the dominant mechanism of spume droplets generation is that of a bag‐breakup fragmentation. Troitskaya et al () and Troitskaya, Druzhinin, et al () developed a statistical description of the bag‐breakup phenomena, but PDF of the drops velocities at injection still remains unknown and requires further research.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, the fetch for wind waves in the ocean is dramatically higher than in a laboratory tank. Besides, the amount of sea spray ejected to the atmosphere, which is also fetch dependent, also can be an order of magnitude higher (see, e.g., Troitskaya, Kandaurov, et al, 2018). The advantage of laboratory experiments is in focusing on a certain physical process behind the phenomenon (in our case, the air‐water fluxes) under control conditions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The problem of dependency of the exchange coefficients in MABL on wind speed is closely connected with the question of the influence of surface waves and spray, that is, the products of wind‐forcing on the exchange of the momentum and mass between the atmosphere and ocean. The effect of waves on the momentum transfer has been studied intensively (see, e.g., Ayet et al, 2020; Husain et al, 2019; Janssen, 1989; Makin et al, 1995; Makin & Mastenbroek, 1996; Makin & Kudryavtsev, 1999; Moon et al, 2004; Takagaki et al, 2012; Takagaki, Komori, & Suzuki, 2016; Takagaki, Komori, Suzuki, et al, 2016; Troitskaya et al, 2012, 2017; Troitskaya, Druzhinin, et al, 2018; Troitskaya, Kandaurov, et al, 2018; Troitskaya & Rybushkina, 2008, and references therein). It has been shown that the momentum transfer by wave disturbances, or the form drag, increases with increasing wind speed due to the widening of the wave spectra.…”
Section: Introductionmentioning
confidence: 99%
“…At present, such an ambitious undertaking is far beyond the art of the possible. There are works which tackle some aspects of the listed elements, for example, viscous decay due to molecular viscosity (Fedorov & Melville 1998), generation of vorticity at the free surface (Hung & Tsai 2009), exact three-dimensional simulation of the Navier-Stokes equations in the absence of wind and turbulence (Hung & Tsai 2009), interaction of waves with a turbulent surface layer (Fedorov & Melville 2009) and the generation of spay (Troitskaya et al 2018).…”
Section: Introductionmentioning
confidence: 99%